The Poetry of Our Lives - Chapman, Michael (Multilingual Margins: A journal of multilingualism from the periphery, 2024)
‘... the passions/of dolphins’ In the mid-1980s at the University of Natal, the student body was overwhelmingly of white, middle class and suburban upbringing. Most had attended well-performing, or reasonably performing, schools. The smattering of Indian and African faces in the lecture halls signalled the unravelling of ‘grand’ apartheid (to use an oxymoron of the time). The parents of these students had probably managed, by whatever means, to enter the peripheries of the white suburbs, or the white economy.